التدقيق الداخلي وأثرة في الحد من ظاهرة غسيل الأموال - كايم ناجي شايب; طالب نادية (Journal of Economics and Administrative Sciences, 2010)
Still Financial institutions, including banks, a key target for money launderers to transfer illicit funds to the legitimate funds and by weaknesses in the internal audit procedures applied in the banks or through a lack of legal structure to combat this phenomenon in addition to the procedures by other regulations The samples from private banks in Baghdad and distributed 35 form to identify the members of these banks who work in the internal audit activity and results appear in the paper that there is direct impact of the internal audit of 60% to curb money laundering, The rest of the figure is attributed to other factors may be legal, administrative or linked to the application of international standards